Die Christologie der Pastoralbriefe - Stettler, Hanna (Mohr Siebeck, 2019)
Was the author of the Pastoral Epistles only a purveyor of other men's Christology? Or is the Christology of the Pastorals the author's own? Does this Christology fall back on a level below Pauline Christology or does it go far beyond it, as some would have it? Hanna Stettler shows that the author was true to Pauline thought by not just repeating what Paul had taught but rather by reinterpreting it for his current time in the Hellenistic language of his days. For this reason the language of incarnation and the parousia is transformed into the scheme of the twofold epiphany of Christ, the Messiah. The author of the Pastorals includes both Synoptic and Johannine thought in order to present a comprehensive picture of the person and work of Jesus Christ.